1999
DOI: 10.1016/s0005-2736(99)00056-5
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethyl ketones and methyl fluorophosphonates as inhibitors of group IV and VI phospholipases A2: structure-function studies with vesicle, micelle, and membrane assays1This paper is dedicated to the memory of Prof. H.M. Verheij.1

Abstract: A series of fatty alkyl trifluoromethyl ketones and methyl fluorophosphonates have been prepared and tested as inhibitors and inactivators of human groups IV and VI phospholipases A(2) (cPLA(2) and iPLA(2)). Compounds were analyzed with phospholipid vesicle-, detergent-phospholipid mixed-micelle-, and natural membrane-based assays, and, with few exceptions, the relative inhibitor potencies measured with the three assays were similar. Ph(CH(2))(4)COCF(3) and Ph(CH(2))(4)PO(OMe)F emerged as a potent inhibitor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 31 publications
3
69
0
6
Order By: Relevance
“…It is known that AACOCF3 not only inhibits cPLA 2 , but also inhibits iPLA 2 and COX-2 (Ghomashchi et al, 1999;Kalyvas and David, 2004). Recently, it has been shown that the inhibitors of cPLA 2 , iPLA 2 and sPLA 2 can all reduce the severity of EAE, and activation of different PLA 2 isoforms may be involved in the different stages of the disease (Kalyvas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that AACOCF3 not only inhibits cPLA 2 , but also inhibits iPLA 2 and COX-2 (Ghomashchi et al, 1999;Kalyvas and David, 2004). Recently, it has been shown that the inhibitors of cPLA 2 , iPLA 2 and sPLA 2 can all reduce the severity of EAE, and activation of different PLA 2 isoforms may be involved in the different stages of the disease (Kalyvas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The compound competes with endogenous phospholipid molecules for the active catalytic site on the PLA 2 enzyme. MAFP has been shown to irreversibly inhibit soluble cytosolic cPLA 2 and iPLA 2 , possibly by phosphorylation of the active site serine residue (Ghomashchi et al, 1999). Although the relatively polar MAFP has direct access to the catalytic site of soluble PLA 2 isoforms, the active site serine residue of membrane-associated iPLA 2 may be "protected" from this inhibitor.…”
mentioning
confidence: 99%
“…Long-chain polyunsaturated fatty acyl fluorophosphonates have been demonstrated previously to irreversibly inactivate phospholipases through rapid phosphorylation of a reactive serine residue in the active site (24,25). Our studies reported here were set in motion by the determination of the X-ray structure of the hFAS TE domain treated with twofold excess of methyl γ-linolenyl fluorophosphonate (MGLFP; Scheme S1) (see Methods and SI Methods).…”
Section: Resultsmentioning
confidence: 99%